Coppicing ability of teak (Tectona grandis) after thinning - Thaiutsa, B.; Puangchit, L.; Yarwudhi, C.; Wacharinrat, C.; Kobayashi, S. (Center for International Forestry Research, 2001)
The research was carried out at the Forest Industry Organization’s Thongphaphum Plantation in Kanchanaburi province, Thailand. The main objective was to determine the effects of different thinning methods on coppicing ability of 17-year-old teak leading to two canopy levels. Teak stumps were planted in 1980 at a spacing of 4 x 4 m and average survival rate was 72%. In 1997 the thinning experiment was set up in a random block design with 3 replications and 4 treatments : low thinning, 1:1 mechanical thinning, 2:2 mechanical thinning, and clear cutting. Average stand density after thinning was 40 trees plot-1, equivalent to 250 trees ha-1. The thinned teak had average diameter breast height (dbh) of 18.5 cm and a commercial volume of 0.2411 m3 tree-1. Thinning methods did not affect shoot density, but affected shoot growth. Three months after thinning, there were 11.6 shoots stump-1. This dropped to 7.9 shoots stump-1 at 1-year-old, due to competition. Average dbh and total height of 1-year-old shoots varied with available space after thinning having maximum figures for clear cutting (dbh 3.2 cm, height 2.91 m), followed by 2:2 thinning (dbh 2.6 cm, height 2.29 m), 1:1 thinning (dbh 2.5 cm, height 2.20 m), and low thinning (dbh 2.1 cm, height 1.75). The findings indicate that shoot growth is promoted by wider gaps after thinning due to the light-demanding characteristics of teak.